Correction of mature skin with the help of decorative cosmetics - Jankauskaitė, Gerda; Gierasimovič, Zita (Slauga. Mokslas ir praktika, 2022)
Beauty products are used to visually conceal visible aging of skin. The appropriate selection of makeup techniques and decorative cosmetics for mature age women help correct their features and conceal skin problems. Aim. The article deals with the effect of cosmetic products on mature face skin. Material and methods. In 2021, as many as 16 publications on the subject under discussion that appeared during the past decade, were analysed. Between 2012 and 2021, articles were published in the databases of the journals Skin Research and Technology, Psychology, Journal of Pharmaceutics, Dermatology, Cosmetics, Journal of Consumer Behaviour. All publications are in the English language, the texts are complete and easily accessible. The selected publications describe the skin aging process, the composition of beauty products, nanotechnology products and the application of cosmetic products to prevent the process of premature skin aging. Recommendations for mature skin care are provided. Results. In the 21st century, cosmetics is widely used and is in great demand in the world market. Annually the demand increases by approximately 4.5 percent. Cosmetic products and make-up make mature face skin look more attractive. Attractive faces are perceived as much younger, the face contour is preserved, skin is firm, the size of the eyes and the area around them, and lip distraction remain unchanged. Cosmetic surgical procedures enhancing the appearance of face skin can improve psychological health of the patients; there is no evidence about how these changes effect a positive attitude of other individuals to their changed appearance, the status of an individual and his/her social wellbeing. Conclusions. 1. Most often scientific literature is concerned with the effect of make-up on the psychological aspect – an individual’s attractiveness. 2. Beauty products and make-up techniques chosen for mature skin change the face in three directions: they change the contours of the face, skin homogeneity, contrast of the face and the size of facial features. 3. Innovative, biologically active cosmetic products have an external and therapeutic benefit to the appearance of face skin, are not only friendly to human skin and health but also are environmentally friendly.